Management of rhizome rot of ginger in Eastern ghat high land zone of Odisha - Sahoo, B B; Senapati, N; Acharya, P; Nayak, L; Behera, B R; Dalei, B B; Meena, M K (Indian Journal of Plant Protection, 2020)
Short Communication